Kondisi Aktual Penguasaan Tanah Ulayat Di Maluku: Telaah Terhadap Gagasan Pendaftaran Tanahnya - Oloan Sitorus (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
Abstract: What land registration concept is suitable for Tanah Ulayat (Petuanan Land)? This question is relevant to be answered when the actual conditions of tenurial of the Petuanan Land have undergone an individualization process. The above question is answered by applying the concept of land registration to the actual conditions of customary land tenure. For Petuanan Land which is still intact containing public authority and private right, the proper concept of land registration is only limited to the Land Register. Furthermor, Petuanan Land that has undergone the process of individualization into Tanah Marga or Soa and individual land, the concept of land registration can be carried out up to the issuance of certificates as proof of land rights. Thus, the portion of Petuanan Land that can be the object of Complete Systematic Land Registration in Maluku Province is Petuanan Land that has undergone a process of individualization, can be land that is possessed or owned  by traditional village (although very rare), clan or soa. Intisari: Pendaftaran Tanah yang bagaimanakah yang tepat bagi Tanah Ulayat (Tanah Petuanan) di Maluku? Pertanyaan ini dipandang relevan untuk dijawab ketika kondisi aktual penguasaan Tanah Ulayat (Tanah Petuanan) itu sudah mengalami proses individualisasi. Pertanyaan di atas dijawab dengan cara menerapkan konsep pendaftaran tanah terhadap kondisi aktual penguasaan tanah ulayat. Bagi Tanah Petuanan yang masih utuh berisi kewenangan publik dan privat, konsep pendaftaran tanah yang tepat hanyalah sebatas Daftar Tanah. Selanjutnya, Tanah Petuanan yang sudah mengalami proses individualisasi menjadi Tanah Marga atau Soa dan Tanah Individual, maka konsep pendaftaran tanah dapat dilakukan sampai pada penerbitan sertipikat sebagai bukti hak atas tanah. Dengan demikian, bagian dari Tanah Petuanan yang dapat menjadi objek Pendaftaran Tanah Sistematik Lengkap di Provinsi Maluku adalah Tanah Petuanan yang sudah mengalami proses individualisasi, dapat berupa tanah yang dikuasai oleh negeri (meskipun sangat jarang), tanah yang dikuasai marga atau soa, dan tanah yang dikuasai oleh perorangan.